2010
DOI: 10.1111/j.1365-2141.2009.07994.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelets release novel thiol isomerase enzymes which are recruited to the cell surface following activation

Abstract: SummaryThe thiol isomerase enzymes protein disulphide isomerase (PDI) and endoplasmic reticulum protein 5 (ERp5) are released by resting and activated platelets. These re-associate with the cell surface where they modulate a range of platelet responses including adhesion, secretion and aggregation. Recent studies suggest the existence of yet uncharacterised platelet thiol isomerase proteins. This study aimed to identify which other thiol isomerase enzymes are present in human platelets. Through the use of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 43 publications
6
97
0
1
Order By: Relevance
“…Activated platelets release PDI and a pool of PDI is found at the platelet cell surface [5]. More recently it has become clear that a range of thiol isomerase enzymes (including PDI, ERp57 and ERp5) become available at the platelet surface following activation [6]. Experiments using mouse models of thrombus formation have highlighted a critical role for PDI [7][8][9], or its close homologue ERp57 (10), in platelet accumulation and fibrin deposition [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Activated platelets release PDI and a pool of PDI is found at the platelet cell surface [5]. More recently it has become clear that a range of thiol isomerase enzymes (including PDI, ERp57 and ERp5) become available at the platelet surface following activation [6]. Experiments using mouse models of thrombus formation have highlighted a critical role for PDI [7][8][9], or its close homologue ERp57 (10), in platelet accumulation and fibrin deposition [11] .…”
Section: Introductionmentioning
confidence: 99%
“…41 Several other groups subsequently demonstrated that thiol isomerases traffic to secretory granules/membrane systems and are released from platelets in an activation-dependent manner. 36,[42][43][44][45] Kim et al showed that platelets lacking PDI have reduced activation-dependent aggregation. 46 Platelet surface PDI has been postulated to modulate a IIb b 3 function, 47 Thiol isomerases have also been found on the surface of the endothelium.…”
Section: Vascular Thiol Isomerasesmentioning
confidence: 99%
“…Several thiol reductases have been identified in vascular cells and may be released into the extravascular space. To evaluate the selectivity of quercetin-3-rutinoside for PDI, we determined its activity against other oxidoreductases (1) known to be secreted from platelets or endothelial cells (17). Quercetin-3-rutinoside failed to inhibit ERp5, ERp57, ERp72, thioredoxin ( Figure 3A), or thioredoxin reductase ( Figure 3B).…”
Section: Introductionmentioning
confidence: 99%